2012
DOI: 10.4236/ojmi.2012.22014
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Exophytic Renal Masses with Determination of the Angular Interface with Renal Parenchyma in US and CT

Abstract: Purpose: To determine whether benign exophytic renal masses can be distinguished from malignant lesions by using the angular interface sign in ultrasonography (US) and computerized tomography (CT). Materials and Methods: A total of 71 cases with exophytic renal mass (2 cm or greater) were examined on the basis of angular interface in US (n = 23), CT (n = 21) and US + CT (n = 16) between January 2008 and June 2010 were included in this study. The renal interface relationships were examined by 2 radiologists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…The variety of lesions was greater in our study, and the different results were obtained about interface types of AMLs and oncocytomas. A similar study also demonstrated that the angular interface could be used as a reliable benignity sign on US and CT [10]. Our results support these studies, with specificity (100%), PPV (100%), and a lower sensitivity (56.16%) than sensitivity ratios of other studies [1,10].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The variety of lesions was greater in our study, and the different results were obtained about interface types of AMLs and oncocytomas. A similar study also demonstrated that the angular interface could be used as a reliable benignity sign on US and CT [10]. Our results support these studies, with specificity (100%), PPV (100%), and a lower sensitivity (56.16%) than sensitivity ratios of other studies [1,10].…”
Section: Discussionsupporting
confidence: 89%
“…Imaging features alone sometimes can be insufficient for differential diagnosis. Although many factors may affect the diagnosis, the characteristics of imaging and quality of examination are important [117].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations